Modeling Infant i's Look on Trial t: Race-Face Preference Depends on i's Looking Style - Thomas, Hoben; Fassbender, Ina (Frontiers in Psychology, 2017)
abstract When employing between-infant designs young infants' looking style (LS) is related to their development: Short looking (SL) infants are cognitively accelerated over their long looking (LL) peers. In fact, LS is a within-infant variable, and depends on infant i's look distribution over trials. For the paired array setting, a model is provided which specifies the probability, π_i[0,1], that i is SL. The model is employed in a face preference study; 74 Caucasian infants were longitudinally assessed at 3, 6 and 9 months. Each i viewed same race (Caucasian) versus other race (African) faces. Infants become SL with development, but there are huge individual differences in rate of change over age. Three month LL infants, π_i<1/2, preferred other race faces. SL infants, π_i>1/2, preferring same race faces at 3, and other race faces at 6 and 9 months. LS changes precede and may control changes in face preference. Ignoring LS can be misleading: Without considering LS, three month infants show no face preference. abstract